Accurate representations of the physicochemical properties of atmospheric aerosols: when are laboratory measurements of value?. (2nd June 2017) - Marsh, Aleksandra; Rovelli, Grazia; Song, Young-Chul; Pereira, Kelly L.; Willoughby, Rose E.; Bzdek, Bryan R.; Hamilton, Jacqueline F.; Orr-Ewing, Andrew J.; Topping, David O.; Reid, Jonathan P.
Abstract : Laboratory studies can provide important insights into the processes that occur at the scale of individual particles in ambient aerosol. We examine the accuracies of measurements of core physicochemical properties of aerosols that can be made in single particle studies and explore the impact of these properties on the microscopic processes that occur in ambient aerosol. Presenting new measurements, we examine here the refinements in our understanding of aerosol hygroscopicity, surface tension, viscosity and optical properties that can be gained from detailed laboratory measurements for complex mixtures through to surrogates for secondary organic atmospheric aerosols.